11x+77=-63+6x

Simple and best practice solution for 11x+77=-63+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x+77=-63+6x equation:


Simplifying
11x + 77 = -63 + 6x

Reorder the terms:
77 + 11x = -63 + 6x

Solving
77 + 11x = -63 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
77 + 11x + -6x = -63 + 6x + -6x

Combine like terms: 11x + -6x = 5x
77 + 5x = -63 + 6x + -6x

Combine like terms: 6x + -6x = 0
77 + 5x = -63 + 0
77 + 5x = -63

Add '-77' to each side of the equation.
77 + -77 + 5x = -63 + -77

Combine like terms: 77 + -77 = 0
0 + 5x = -63 + -77
5x = -63 + -77

Combine like terms: -63 + -77 = -140
5x = -140

Divide each side by '5'.
x = -28

Simplifying
x = -28

See similar equations:

| 0.02(y-8)+0.20y=0.14y-0.7 | | 10000x=80+4x+0.1x^2 | | -7(3x-1)=-91 | | 6(20-5)= | | p-4.9=24.9 | | 27-15=3(37+2x) | | 3m+1=2m | | 0.4x-0.9x-19=1 | | 0.12(0.04)= | | 9x-y+1=0 | | 4x^2+5x=11 | | 2x-1-x=-2 | | 5b+6-64+2=19 | | 2x+9/6=11 | | j-18.5=19.6 | | -51k=65 | | 2x(18x+1)=2x+25 | | 3x*30=5x | | -(6-x)=24 | | 6c-5=5.0(6+4c) | | 11(k-1)=7(k-7) | | 6x^2+11x=8 | | 6c-5=2(6+4c) | | 16=-3(2x+1)+7x | | 20x^4-21x^2+1=0 | | 2x^2+16x=5x+21 | | In(x^4)-In(x^2y)+In(y^2)=0 | | e-29.3=14.5 | | 5x=30*3x | | 2x-14=2x-17 | | p-13.7=47.8 | | x*x=3x+10 |

Equations solver categories